Glucosamine and chondroitin sulfate supplementation to treat symptomatic disc degeneration: Biochemical rationale and case report - van de Nes Jos CM; Wuisman Paul IJM; van Blitterswijk Wim J (BMC, 2003)
Abstract Background Glucosamine and chondroitin sulfate preparations are widely used as food supplements against osteoarthritis, but critics are skeptical about their efficacy, because of the lack of convincing clinical trials and a reasonable scientific rationale for the use of these nutraceuticals. Most trials were on osteoarthritis of the knee, while virtually no documentation exists on spinal disc degeneration. The purpose of this article is to highlight the potential of these food additives against cartilage degeneration in general, and against symptomatic spinal disc degeneration in particular, as is illustrated by a case report. The water content of the intervertebral disc is a reliable measure of its degeneration/ regeneration status, and can be objectively determined by Magnetic Resonance Imaging (MRI) signals. Case presentation Oral intake of glucosamine and chondroitin sulfate for two years associated with disk recovery (brightening of MRI signal) in a case of symptomatic spinal disc degeneration. We provide a biochemical explanation for the possible efficacy of these nutraceuticals. They are bioavailable to cartilage chondrocytes, may stimulate the biosynthesis and inhibit the breakdown of their extracellular matrix proteoglycans. Conclusion The case suggests that long-term glucosamine and chondroitin sulfate intake may counteract symptomatic spinal disc degeneration, particularly at an early stage. However, definite proof requires well-conducted clinical trials with these food supplements, in which disc de-/regeneration can be objectively determined by MRI. A number of biochemical reasons (that mechanistically need to be further resolved) explain why these agents may have cartilage structure- and symptom-modifying effects, suggesting their therapeutic efficacy against osteoarthritis in general.